A meta-level approach to the analysis of legal phenomena based on the key concept of reduction - Smith, Clara Patricia (2003)
In this paper we show how the alleged relationship between AI and Law exhibits an example of reductions of a relevant kind. We put forward a methodological approach, based on the key epistemological concept of reduction, to the understanding, explanation and conceptualisation of phenomena concerning legal systems. This approach is appropriate as a meta-analysis of what happens when we work, think and deal with the many several aspects of legal systems, not only from purist but also from pragmatic points of view. We introduce an epistemological vision of relevant Law-AI connections.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
International Conference on Artificial Intelligence and Law (9a : 2003 jun. 24-28 : Edimburgo). Proceedings. Nueva York : ACM, 2003, pp. 107-108
Keywords: DERECHO; INTELIGENCIA ARTIFICIAL